MANAGEMENT OF TRACHEO BRONCHIAL FOREIGN BODIES IN CHILDREN - Ghani, Rehman; Akhtar, Saleem; Gillani, Syed Mushtaq Ahmed; Nabi, Ghulam (Journal of Ayub Medical College Abbottabad, 1998)
This is a study of 32 cases of foreign body tracheobronchial tree in children, spread over two years' period. More than 65 % of patients were of two years and below. The male to female ratio was 2:1. More than 70% of foreign bodies were vegetable in nature. Foreign bodies were located more often in the right main bronchus as compared to the left (3:2). In all cases, foreign bodies were removed under G.A., with the help of rigid pediatric bronchoscopes. There was no mortality. In 04 cases no history of foreign body inhalation was forthcoming and bronchoscopy was done because the child had persistent cough and episodes of dysphonia. There was a delay of 1-10 days before presentation in the majority of patients. Majority of the patients presented 24 hours after the inhalation of foreign body. Removal of foreign body tracheobronchial tree through rigid bronchoscope under GA is a safe and lifesaving procedure with good results.